Effects of temperature and drought stress on the seed germination of a peatland lily (Lilium concolor var. megalanthum) - Guo, Mingfan; Zong, Jing; Zhang, Jinxin; Wei, Li; Wei, Wenguang; Fan, Rongyang; Zhang, Tingting; Tang, Zhanhui; Zhang, Gang (Frontiers in Plant Science, 2024)
Sexual reproduction through seeds is an effective way to renew plant populations and increase their genetic diversity, but seed germination process is complicated and relatively difficult due to the restriction of environmental conditions. Wetland plants that reproduce sexually through seeds may be affected by changes in moisture and temperature. This study aims to explore the ecological adaptation strategies of seed germination of Lilium concolor var. megalanthum under different hydrothermal conditions. Controlled experiments were conducted to investigate the germination performance of L. concolor var. megalanthum seeds at different temperatures (10°C, 15°C, 20°C, 25°C, and 30°C) and simulated drought stress conditions using PEG-6000 solutions (0%, 5%, 10%, 15%, and 20%). The results showed that temperature, drought stress, and their interaction significantly affected the days to first germination, germination percentage, coefficient of germination rate, germination energy, germination index, and vigor index of seeds (p<0.01). The germination percentage, germination index, and vigor index of seed were significantly higher at 25°C compared to other temperatures (p<0.01). The interaction between low temperature and drought stress significantly delayed the days to first germination. The inhibition of drought stress on seed germination was enhanced by PEG-6000 solution under high temperature. Under the conditions of 25°C and 5% PEG-6000 solution concentration, seeds of L. concolor var. megalanthum exhibited optimal germination parameters. At 10°C and 15°C, the seeds exhibited the highest tolerance to PEG-6000-simulated drought stress. Rehydration germination results showed that extreme temperatures and drought stress conditions inhibit seed germination of L. concolor var. megalanthum without damaging seed structure. The germination pattern of seeds under variable temperature and drought stress conditions reflects their adaptive strategies developed over long-term evolution to cope with the environmental conditions.